Pengetahuan dan amalan pemeriksaan Sendiri payudara (psp) dalam kalangan wanita di Mukim Bujang, Kuala Muda/Yan, Kedah - Jamaliah, Arshad (PPSP, Universiti Sains Malaysia, 2007)
Purposes of this study are to determine knowledge and practice of breast selfexamination among women in Mukim Bujang, Kuala Muda!Yan, Kedah. A crosssectional study was carried out in November and Disember 2006, among women age 18 and above in Mukim Bujang, Kula Muda!Y an, Kedah. A total of 283 respondents, who had completed a validated, interviewer guided questionnaires assesing their knowledge and practice of breast self examination, were selected using multistage cluster sampling. The questionaire consisted of 3 domains namely the socio demographic and economic status, knowledge on bresat self examination and breast cancer and practice of proper techniques to perform breast self examination. True, false and not sure options were given for knowledge questions. Yes and no options were given for practice questions. In order to ensure good reliability, only one dedicated interviewer was involved. Majority of the respondents' age were between 36-55 year old (60%), had secondary education level (63%), housewife (56%), married (86%), and taking oral contraceptive pills (61 %). In general, all respondents have heard about breast self-examination but only 73.9% have ever practice it. Out of this only 1.8% had satisfactory knowledge about proper breast self examination techniques. Chi-square statistical tests showed significant association between those who practice breast self-examination with age, higher education level, married status, higher socio economic group, higher knowledge score on breast self examination techniques and knowledge on risk factors for breast cancer. The same independent variables were found to be predictors for performing breast self examination when analyzed using univariate logstic regression. However, only three factors which are age, not taking oral contraceptive pills, and knowledge on breast self-examination remained signifiantly influenced through multiple logistic regression. Having knowledge on proper techniques is crucial for women in order to ensure their performance on breast self examinations are effective in detecting abnormality during the examinations.